Hydrometallurgical extraction of TiO2 from iron sand for industrial raw material - Sukmara, Sony; Manaf, Azwar; Adi, Wisnu Ari; Putra, Adi Ganda (Politeknik Negeri Lhokseumawe, 2025)
Titanium dioxide (TiO2) is an essential raw material widely used in Indonesia’s medical, cosmetic, paint, cement, aerospace, and defense industries. Despite its industrial importance, domestic TiO2 production remains limited, resulting in continued dependence on imports. Meanwhile, Indonesia possesses abundant iron sand resources that have not been fully utilized as potential raw materials for TiO2 extraction. This study aims to extract titanium dioxide from iron sand obtained from the southern coast of Lebak Regency, Banten Province. The extraction process began with the preparation of iron sand through washing, drying, and magnetic separation to isolate titanium-rich minerals, mainly ilmenite (FeTiO3) and titanomagnetite (Fe2TiO4). The ilmenite concentrate was leached using sulfuric acid (H2SO4, 96%) at 150–200 °C, forming titanium oxysulfate (TiOSO4) and ferrous sulfate (FeSO4). The solution was filtered, and titanium was precipitated as hydrated titanium dioxide (TiO2•H2O) through neutralization. The precipitate was washed, dried, and calcined at 500 °C to obtain anatase-phase TiO2. X-ray diffraction (XRD) analysis revealed dominant mineral phases of ilmenite (98.63%) and titanomagnetite (90.56%), while X-ray fluorescence (XRF) showed titanium contents of 22.72% in FeTiO3 and 20.45% in Fe2TiO4. The resulting TiO2 exhibited an anatase phase with 98.7% purity. The findings confirm that Lebak’s southern coastal iron sand is rich in titanium-bearing minerals, demonstrating its potential as a sustainable raw material for domestic TiO2 production. This study provides a preliminary foundation for optimizing the extraction process to enhance yield and support local industrial development.